FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 6-12 BULAN DI WILAYAH KERJA PUSKESMAS CIJAGRA LAMA - Enisah; Yunita Sarah Nadeak; Andi sukandi (LPPM Akper Kebonjati, 2023)
The coverage of babies breastfed by exclusive ASI in 2022 was 55.7%, while in West Java in 2022 was 33%, and in the working area of Sigalingging Puskesmas was 4.1%. The objective of the research was to find out some factors which were correlated with breastfeeding 6-12 month-old babies with exclusive ASI in the Working Area of Cijagra Lama Puskesmas,. The research used observational analytic method with cross study. The population was 95 women who had 6-12 month-old babies in the Working Area of Cijagra Lama Puskesmas, and all of them were used as the samples, taken by using total sampling technique. The data were analyzed by using univariate analysis, bivariate analysis with chi square test, and multiple logistic regression analysis. The result of the research showed there was the correlation of knowledge, husbands’ support, physical and mental preparation, health care providers, and socio-culture with breastfeeding with exclusive ASI. It is recommended the Puskesmas management provide counseling about exclusive ASI for pregnant women and their husbands.